The Gender Disparity in Computer Use: Does It Really Exist? - Everett, Cristen (Valdosta State University, 2004)
The purpose of the study was to determine if there is a gender disparity in proficiency and attitudes toward computer use among students at my school enrolled in a basic computer class while learning a new software program via class instruction. Twenty-three female students and twenty male students participated in the study, during which students received instruction on using Microsoft Access, a new software program for them. The study contained both quantitative and qualitative elements. For the quantitative portion, students completed a Microsoft Access assessment to determine if there was a gender disparity in student knowledge and skill level in using Access. They also took pre and post attitude surveys to determine their attitudes toward computer use in general and toward the Microsoft Access learning experience. Teacher observations during class and peer interviews were utilized for the qualitative portion of the study. The findings indicate there is not a gender disparity associated with attitudes about computer use in general or proficiency with using a new software program, but there may be a slight gender disparity associated with attitudes toward learning a new software program. Males reported feeling slightly more confident about using a new software program than females. The results of the study were communicated to other Career and Technology teachers at a department meeting.
Keywords: Gender disparity; Microsoft Access; Skill level; Student knowledge; Computers and women; Sex differences in education; Computers--Study and teaching